Assessment of endophyte-derived tremorgenic compounds in Ipomoea asarifolia using mouse models. (15th December 2018) - Welch, K.D.; Pfister, J.A.; Cook, D.; Carriao dos Santos, F.; Lee, S.T.
Abstract: Ipomoea asarifolia has been associated with a tremorgenic syndrome in livestock. Recently indole diterpene compounds were identified in I. asarifolia, some of which have been shown to cause a tremorgenic syndrome. In this study, the tremorgenic nature of I. asarifolia was assessed using a mouse model. Adult mice were fed rodent chow containing 10, 15, 20 and 25% endophyte infected (E+), or 25% endophyte free (E-), I. asarifolia for 14 days. The mice fed E+ chow developed a tremorgenic syndrome as characterized by visually observed muscle tremors and an inability to traverse a balance beam, whereas the mice fed E- chow did not develop tremors and had similar muscle coordination to control mice. A lactating mouse model was also used to determine if the compounds can be transferred to nursing pups via the milk. Nursing pups were exposed via their mother's milk for 21 days, from post-natal day 0–21. The pups from dams exposed to E+ chow developed a similar tremorgenic syndrome. Data presented in this study demonstrate that the tremorgenic compounds in I. asarifolia are endophyte derived. Additionally, both adult mice and nursing pups are good models for studying the tremorgenic nature of I. asarifolia and related plants. Highlights: Indole diterpenes are the primary tremorgenic principles in I. asarifolia. Mice can be used as a small animal model to study the tremorgenic nature of I. asarifolia. I. asarifolia causes a dose-dependent physiological response that results in visually observable muscle tremors. The tremorgenic compounds in I. asarifolia are transferred via milk to nursing young causing muscle tremors in the pups. The muscle tremors caused by I. asarifolia are transient in nature, as they appear to resolve quickly once exposure stops.